2017
DOI: 10.1016/j.ekir.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

What Genetics Tells Us About the Pathogenesis of IgA Nephropathy: The Role of Immune Factors and Infection

Abstract: Immunoglobulin A nephropathy (IgAN) is the most common type of primary glomerulonephritis, which is characterized by IgA1-containing immune-deposits in the glomerular mesangium. The epidemiologic observations of familial clustering as well as ethnic and regional discrepancies indicate a genetic component to IgAN. Large, international, genome-wide association studies have identified several susceptibility genes and loci for IgAN, many of which have been implicated in immune regulation and are shared with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 99 publications
1
24
0
Order By: Relevance
“…31 The risk alleles that were common across these population groups were those involved in the regulation of adaptive immunity (major histocompatibility complex), complement activation (CFH, CFHR3-1, ITGAM-ITGAX), mucosal innate immunity (DEFA, CARD9, VAV3, ODF1-KLF10, UBR5) and in the regulation of mucosal IgA production (TNFSF13, HORMAD2, ST6GAL1). 32 However, risk alleles demonstrating variants coding for MEGSIN, DEFENSINS and TNF SF13/APRIL have been demonstrated to be associated with IgAN susceptibility in Chinese cohorts but not Europeans. 33,34 The observation that genetic susceptibility loci associated with IgAN have only been reported in Asian, but not only in Europeans, explains in part the differences in observed prevalence, but also calls into question if the pathogenic processes in the "disease" is indeed the same in different populations across different areas.…”
Section: Association Between Genetic Susceptibility and Frequency Of mentioning
confidence: 99%
See 1 more Smart Citation
“…31 The risk alleles that were common across these population groups were those involved in the regulation of adaptive immunity (major histocompatibility complex), complement activation (CFH, CFHR3-1, ITGAM-ITGAX), mucosal innate immunity (DEFA, CARD9, VAV3, ODF1-KLF10, UBR5) and in the regulation of mucosal IgA production (TNFSF13, HORMAD2, ST6GAL1). 32 However, risk alleles demonstrating variants coding for MEGSIN, DEFENSINS and TNF SF13/APRIL have been demonstrated to be associated with IgAN susceptibility in Chinese cohorts but not Europeans. 33,34 The observation that genetic susceptibility loci associated with IgAN have only been reported in Asian, but not only in Europeans, explains in part the differences in observed prevalence, but also calls into question if the pathogenic processes in the "disease" is indeed the same in different populations across different areas.…”
Section: Association Between Genetic Susceptibility and Frequency Of mentioning
confidence: 99%
“…The observed differences in the frequency of IgAN in different ethnic populations mirrored the geographic differences in the prevalence of genetic susceptibility and protective loci, providing a biologically plausible explanation for the observed differences . The risk alleles that were common across these population groups were those involved in the regulation of adaptive immunity (major histocompatibility complex), complement activation (CFH, CFHR3‐1, ITGAM‐ITGAX), mucosal innate immunity (DEFA, CARD9, VAV3, ODF1‐KLF10, UBR5) and in the regulation of mucosal IgA production (TNFSF13, HORMAD2, ST6GAL1) . However, risk alleles demonstrating variants coding for MEGSIN, DEFENSINS and TNF SF13/APRIL have been demonstrated to be associated with IgAN susceptibility in Chinese cohorts but not Europeans .…”
Section: Association Between Genetic Susceptibility and Frequency Of mentioning
confidence: 99%
“…First, the clinical observation and genetic studies have suggested the role of mucosal immunity in IgAN . The distal ileum‐targeting released budesonide reduced proteinuria in patients with IgAN, indicating the efficacy of targeting intestinal mucosal immunity upstream of disease manifestation .…”
Section: Novel Approaches In Igan: Targeting Pathogenic Pathway Therapymentioning
confidence: 99%
“…First, the clinical observation and genetic studies have suggested the role of mucosal immunity in IgAN. 13,14 The distal ileum-targeting released budesonide reduced proteinuria in patients with IgAN, indicating the efficacy of targeting intestinal mucosal immunity upstream of disease manifestation. 3 Second, considering that B-cell activation may be involved in the production of Gd-IgA1 and its antibodies in IgAN, targeting B-cell pathway treatment, such as rituximab (NCT00498368), blisibimod (NCT02062684), atacicept (NCT02808429), is an appealing therapeutic option.…”
Section: Novel Approaches In Igan: Targeting Pathogenic Pathway Therapymentioning
confidence: 99%
“…Lai (6) and Suzuki et al (7) reviewed the previous studies and discussed the pathogenesis of IgAN in details, and they considered that four hits are needed for the kidney injure of IgAN patients. The first hit is the production of galactose-deficient IgA1 (8)(9)(10), which has been reported widely to be genetically determined (11) (12); the second hit is the production of antiglycan antibodies, which mainly is the IgG and IgA subtypes, and can specifically bind the under galactosylated IgA1; the third hit is formation of IgA immune complex, which then deposit in the mesangium; the fourth hit is the activation of mesangial cells by immune complex, which can proliferate and secrete extracellular matrix, cytokines, and chemokines, and then activate the alternative complement pathway and result in renal injury. In fact, it is widely accepted that the IgAN is an immune related disease with the involvement of the whole immune system, and except of the B cells and antibody, the T cells also play important roles in the disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%